Employers' Perspective On Employability Skills: An Exploratory Study On Management Students (International Journal of Food and Nutritional Sciences, 2022)
A certain set of skills, including hard, soft, technical, and transferable skills, make up the concept of employability. Additionally, employability is viewed as a process as well as a product because it is a set of abilities that "enables" and "empowers" a person to develop marketable abilities that can result in gainful employment.There is currently a lot of interest in research on employment difficulties. There are now fewer available work possibilities. Right now In the urbanisation era, employers are more picky when employing graduates and look for those who have the cultural competence, interpersonal skills, teamwork, and decision-making aptitudes necessary in today's global market.The present study moves further by offering a thorough review of the employability abilities of management students from the viewpoint of employers. It has taken into account 20 studies. It also includes a literature evaluation with the goal of identifying key factors that have an impact on management graduate employability. The study's goal is to identify several indicators of employable abilities and their critical importance in the workplace, taking into account the employer's point of view. The results of this review of the literature highlight the critical competencies that management graduates must possess in order to meet industry expectations. They also confirm that it is the duty of the management institute to foster the development of technical and professional competencies that will increase the employability of management students.